2022
DOI: 10.3389/fphar.2022.832929
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Therapy of Pharmacoresistant Epilepsies: The Role of Fenfluramine

Abstract: Epilepsy is among the most common neurological chronic disorders, with a prevalence of 0.5–1%. Despite the introduction of new antiepileptic drugs during recent years, about one third of the epileptic population remain drug-resistant. Hence, especially in the pediatric population limited by different pharmacokinetics and pharmacodynamics and by ethical and regulatory issues it is needed to identify new therapeutic resources. New molecules initially used with other therapeutic indications, such as fenfluramine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Fenfluramine has been shown to offer significant improvement in DS patients, possibly via multiple mechanisms of action (47). For example, fenfluramine acts to increase serotonin release by inhibiting its reuptake while also inhibiting several classes of serotonin receptors such as 5HT-1D and 5HT-2A/C (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fenfluramine has been shown to offer significant improvement in DS patients, possibly via multiple mechanisms of action (47). For example, fenfluramine acts to increase serotonin release by inhibiting its reuptake while also inhibiting several classes of serotonin receptors such as 5HT-1D and 5HT-2A/C (48).…”
Section: Discussionmentioning
confidence: 99%
“…The functional deficit in the patient-derived SSs could be rescued to some extent by acute application of fenfluramine as assessed by two-photon calcium imaging (Figure 4G-H). Fenfluramine has been shown to offer significant improvement in DS patients, possibly via multiple mechanisms of action (47). For example, fenfluramine acts to increase serotonin release by inhibiting its reuptake while also inhibiting several classes of serotonin receptors such as 5HT-1D and 5HT-2A/C (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from DS and LGS, studies on FFA for the treatment of other DREs are also ongoing ( 15 ). A small sample size study of FFA for CDD conducted by Devinsky et al ( 14 ) recruited six patients with CDD and initially demonstrated that 0.4 mg/kg/d and 0.7 mg/kg/d FFA decreased seizure frequency with no distinct adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…No serious adverse effects, such as lethal cardiac disease, were observed in any of these studies. Meanwhile, another study applying FFA as an adjunct to the treatment of five different types of developmental and epileptic encephalopathies (DEEs) (SYNGAP1 Encephalopathy, STXBP1 Encephalopathy With Epilepsy, Inv Dup ( 15 ) Encephalopathy, Multifocal or Bilateral Malformations of Cortical Development, Continuous Spike and Waves During Slow Sleep) is also enrolling patients in a non-controlled clinical trial (NCT05232630), which focuses on assessing seizure frequency, intensity, and duration before and after FFA treatment. Moreover, “non-epileptic outcomes,” such as variations in cognitive activity, level of alertness, impulsivity/self-control, gait stability, and other alterations may also be detected during the interview and physical examination.…”
Section: Discussionmentioning
confidence: 99%